The Effect of Transformational Leadership on Business Performance Through Business Agility Expedition Services - Permana, Erwin (Jurnal Manajemen Teknologi, 2022)
Abstract. The Covid-19 pandemic has put pressure on various business sectors because social distancing policies have resulted in significantly reduced interactions between humans. So expedition services are the choice to meet most human needs. So that the shipping service business is a business that is experiencing rapid development during the pandemic. This study aims to analyze: 1) the influence of transformational leadership on the business performance of courier service, 2) the influence of transformational leadership on the business agility of courier service, 3) the influence of business agility on the business performance of courier service. The analysis technique used Structural Equation Model (SEM) with SmartPLS. The data was collected through the dissemination of questionnaires. Research respondents are shipping service companies with the criteria for joining the Association of Indonesian Express, POS and Logistics Delivery Service Companies (ASPERINDO). The results of the analysis showed that transformational leadership affects performance; transformational leadership affects business agility, and agility affects the company's performance. The results of the statistic test showed that all constituent dimensions of the model are at a high level. It means that the results of this study confirmed that the Covid-19 pandemic becomes a blessing for the courier service business. People's habits of shopping online during the pandemic are believed to not be significantly reduced even though the pandemic is over. This research recommends courier service companies maintain market agility and operational agility by improving digital capacity. In the future, research that involves the digital capability of the courier service business is needed during the pandemic.Keywords: Transformational leadership, agility, performance, courier service, COVID-19Abstrak. Pandemik Covid-19 telah memberikan tekanan on berbagai sektor bisnis karena kebijakan social distancing mengakibatkan interaksi antar manusia berkurang significant. Maka jasa ekspedisi menjadi pilihan untuk memenuhi sebagain besar kebutuhan manusia. Sehingga bisnis jasa ekspedisi menjadi bisnis yang mengalami perkembangan pesat selama pandemik. Penelitian ini bertujuan untuk menganalisis: 1) pengaruh transformational leadership on performancebisnis jasa ekspedisi, 2) pengaruh transformational leadership on business agility jasa ekspedisi, 3) pengaruh business agility on business performance jasa ekspedisi. Teknik analisis menggunakan Structural Equation Model (SEM) with SmartPLS. Data dikumpulkan melalui penyebaran questionnaire. Respondents penelitian adalah perusahaan jasa ekspedisi dengan kriteria tergabung di dalam Asosiasi Perusahaan Jasa Pengiriman Ekspres, POS and Logistik Indonesia (ASPERINDO). Jumlah respondents penelitian sebanyak 79 orang, dengan satu perusahaan diwakili oleh satu respondents. Hasil analisis menunjukkan that transformational leadership berpengaruh on kinerja; transformational leadership berpengaruh on business agility; Agilityberpengaruh on company performance. Hasil uji statistik menunjukkan that semua dimensions penyusun model berada pada level yang tinggi. Artinya, hasil penelitian ini mengkonfirmasi that pandemik covid-19 menjadi berkah bagi bisnis jasa ekspedisi. Kebiasaan masyarakat berbelanja secara online dimasa pandemic diyakini tidak akan berkurang significant meskipun pandemic sudah berakhir. Oleh karena itu penelitian ini merekomendasikan kepada perusahaan jasa ekspedisi untuk menjaga Agilitypasar maupun Agilityoperasional dengan meningkatkan kapabilas digital. Kedepan diperlukan penelitian yang melibatkan kapabilitas digital usaha jasa eksepedisi dimasa pandemik.Kata kunci: Transformational leadership, agilitas, kinerja, jasa ekspedisi, COVID-19